THE ROLE OF TEACHERS IN IMPLEMENTING ONLINE ENGLISH CLASSES DURING THE COVID-19 PANDEMIC AT SMA NEGERI 1 TARAKAN - Candra, Luki; Arifin, Arifin; Kusmaryani, Woro (Borneo Journal of English Language Education, 2021)
This study attempted to characterize the prominent role of English teachers and studentresponses in online lessons during the Covid-19 pandemic at SMA Negeri 1 Tarakan.A descriptive design with a qualitative approach was utilized in the research, whichdescribed the actual situation in the field. The researcher employed interviewprotocols, questionnaires, observation sheets, and documentation to gather the data.Five English teachers and students from class XI Linat A (27 students) from SMANegeri 1 Tarakan served as the researcher participants in this study. Informer,Organizer, Motivator, Director, Mediator, Evaluator, Advisor, Diagnostician, andFacilitator were the most common positions identified by the researcher, and studentsresponses matched the nine functions played by the teacher. During their onlineEnglish Classes, the students expressed their honest feelings to their teacher. Inconclusion, the findings of this study had provided the answer to the research problems.